On the move to stay current: Knowledge cycling and scheduled labor mobility. Issue 4 (September 2018) - Pantic-Dragisic, Svjetlana; Söderlund, Jonas
Technical consulting plays an increasingly important role in developing and transferring knowledge in a wide range of industries and sectors. We present a case study of Swift Tech, a leading Scandinavian technical consulting firm, to identify and assess the importance of knowledge cycling —a knowledge process based on scheduled and recurrent rotation of technical consultants among organizational and problem-solving contexts. Our study identifies four main phases of knowledge cycling: entering an assignment, building experience, contributing to the project, and shifting to a new assignment. These phases underpin our model of knowledge cycling, which demonstrates that two aspects of local knowledge processes are critical: project task familiarization and project organization familiarization. We show that knowledge cycling relies on a dynamic interaction between client organization, consulting firm, and individual consultant in the ongoing transfer of knowledge among distinct contexts and communities. Knowledge cycling demonstrates the significance of "mobile knowledge" for the development of situated knowledge; hence, our results have important implications for situated learning theory.